A new formula consisting of the five-factor score and earliest vasculitis damage index at diagnosis for predicting poor outcomes of antineutrophil cytoplasmic antibody-associated vasculitis - Ha, Jang Woo; Kwon, Oh Chan; Park, Yong-Beom; Lee, Sang-Won (Frontiers in Medicine, 2025)
BackgroundThis study aimed to investigate whether a new formula consisting of more than two antineutrophil cytoplasmic antibody-associated vasculitis (AAV)-specific indices at diagnosis could predict poor outcomes during follow-up in patients with AAV.MethodsThis study included 323 patients first diagnosed with AAV. AAV-specific indices included the Birmingham vasculitis activity score (BVAS), the five-factor score (FFS), and the earliest vasculitis damage index (eVDI). Poor outcomes included all-cause mortality, end-stage kidney disease (ESKD), cerebrovascular accident (CVA), and acute coronary syndrome (ACS). The four formulas were created by adding each index: BVAS + FFS + eVDI, BVAS + FFS, BVAS + eVDI, and FFS + eVDI.ResultsThe median age was 61.0 years (36.2% men). Among the four formulas, FFS + eVDI at AAV diagnosis exhibited the highest area under the curves (AUCs) for all-cause mortality and ESKD in receiver operating characteristic curve analysis. When the optimal cut-off was determined as 4.5 for all-cause mortality and ESKD simultaneously, patients with FFS + eVDI ≥4.5 at AAV diagnosis exhibited significantly higher risks for both all-cause mortality and ESKD, and lower cumulative patients’ and ESKD-free survival rates than those without. in multivariable Cox analyses with other variables at AAV diagnosis, FFS + eVDI at AAV diagnosis was proven to be an independent predictor for all-cause mortality and ESKD during follow-up in patients with AAV.ConclusionThis study demonstrated that a new formula consisting of FFS and eVDI at AAV diagnosis could effectively predict both all-cause mortality and ESKD during follow-up in patients with AAV.